2012
DOI: 10.5897/ajpp12.567
|View full text |Cite
|
Sign up to set email alerts
|

Efficacious formulation of anti-malarial dry suspension for pediatric use

Abstract: This study was designed for concealing the bitter taste of an anti-malarial drug, artemether, by using various coating substances. Four granular formulations (formulations A, B, C and D) of artemether were prepared using different excipients and then were coated using methocil™ E5 and opadry ® enteric solutions in a simple coating pan. In the initial 2 min, the cumulative percentage amount of drug release in phosphate buffer at pH 6.8 from pure artemether and formulation A, B, C and D was 59.4 ± 4.2, 55.7 ± 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Correspondingly, manual taste perception evaluation indicated that the bitter taste intensity score of Opadry ® Enteric-coated granules was much lower than that of Methocil™ E5-coated granules (47.3 vs. 80.5), further confirming the superior taste-masking effect of the Opadry ® Enteric coating. In another investigation, the same two coating materials were also used to enclose particles of a dry suspension containing another artemisinin derivative (named artemether) for taste-masking [ 40 ]. Similarly, the superior taste-masking effect was achieved by the Opadry ® Enteric coating.…”
Section: Physical Maskingmentioning
confidence: 99%
“…Correspondingly, manual taste perception evaluation indicated that the bitter taste intensity score of Opadry ® Enteric-coated granules was much lower than that of Methocil™ E5-coated granules (47.3 vs. 80.5), further confirming the superior taste-masking effect of the Opadry ® Enteric coating. In another investigation, the same two coating materials were also used to enclose particles of a dry suspension containing another artemisinin derivative (named artemether) for taste-masking [ 40 ]. Similarly, the superior taste-masking effect was achieved by the Opadry ® Enteric coating.…”
Section: Physical Maskingmentioning
confidence: 99%
“…One of the methods to achieve the maximum taste masking characteristic is to formulate the drug in suspension form which creates a physical fence around the drug [15, 16]. The objective of this work was to formulate acetaminophen as a relatively stable liquid form and study the influence of different polymers such as CMC, Veegum, tragacanth, and PVP on its rheologic characteristics.…”
Section: Introductionmentioning
confidence: 99%